Alcohol, liver disease, and transplantation: shifting attitudes and new understanding leads to changes in practice. Issue 2 (April 2018) - Mathurin, Philippe; Lucey, Michael R.
Abstract : Purpose of review: Review the current status of liver transplantation for patients with alcohol use disorder (AUD). Recent findings: Alcohol-related liver disease (ALD) will increase as a source of patients requiring liver transplantation. Attitudes to use of liver transplantation as rescue therapy for patients with severe alcohol-related hepatitis are changing. The long-term health of ALD liver transplantation recipients requires continued assistance to patients with AUD. Summary: Liver transplantation of patients with ALD increased during the last decade and we predict that this trend will continue because of the decline in the number of hepatitis C virus-infected candidates. Concomitantly, a shift in the selection for liver transplantation has occurred of patients with severe alcohol-related hepatitis not responding to medical therapy. Although rescue liver transplantation is a valuable option for patients with severe alcohol-related hepatitis, worldwide practice regarding rescue liver transplantation remains very heterogeneous. There is increasing recognition that excessive consumption of alcohol after liver transplantation is harmful to graft function and patient survival. Factors associated with relapse are younger age at liver transplantation and shorter duration of sobriety prior to liver transplantation. The long-term health of the ALD liver transplant recipient requires continued assistance regarding AUD, a lifelong disorder of craving, relapse, and remission. However, there have been very few studies evaluating best practices for long-term addiction care in transplant recipients. After liver transplantation, the prevalence of cardiovascular disease, infections, and cancer increases over time. Addiction to tobacco constitutes an important issue that must be considered as tobacco cessation may decrease the incidence of tobacco-related cardiovascular and lung disease and aerodigestive cancers.